Case Report: Successful treatment of severe type II decompression sickness characterized by multiple gas emboli - Wang, Yan; Wang, Yujie; Li, Shuping; Ai, Donghua; Chen, Yubo; Jing, Mei (Frontiers in Medicine, 2025)
BackgroundDecompression sickness (DCS) is usually caused by inadequate decompression. Although adherence to decompression protocols can significantly reduce the incidence of DCS, it still cannot prevent all cases from occurring. If a large number of gas bubbles enter the right heart and pulmonary arterial system, patients may present with symptoms such as cough, tachypnea, chest pain, dyspnea, or even shock. The presence of numerous bubbles in the abdominal cavity and portal venous system may also lead to liver dysfunction or abdominal pain. Theoretically, DCS occurring after dives that follow decompression tables should be relatively mild. The development of severe Type II DCS characterized by multiple gas emboli following protocol adherence is considered rare.Case presentationWe report a case of a diver who developed severe Type II DCS characterized by multiple gas emboli despite conservative adherence to a decompression protocol. The maximum dive depth was 19 meters, with a total dive duration of 120 min. His underwater task involved heavy lifting, and he performed decompression conservatively according to the Chinese Air Diving Decompression Table for decompression, with a total decompression time of 45 min. However, 30 min after surfacing, the patient developed symptoms including chest tightness, shortness of breath, dyspnea, fatigue, and pain in the left knee and thigh. Computed tomography (CT) scans of the chest and abdomen revealed gas emboli in multiple locations, including the pulmonary artery, right ventricle, and hepatic portal vein. The patient recovered completely after timely recompression therapy and was discharged.ConclusionThis report highlights the unpredictability of DCS; even when decompression tables are followed, severe Type II DCS may occur if the diver’s underwater workload is excessive and multiple risk factors are present. Prompt recompression therapy is crucial to prevent clinical deterioration. Due to the limitations of current DCS models, further research is needed to develop individualized safe decompression protocols based on physiological variables.